Chronic 5-HT3 receptor antagonism ameliorates seizures and associated memory deficit in pentylenetetrazole-kindled mice. (17th December 2016) - Mishra, Awanish; Goel, Rajesh Kumar
Highlights: Ondansetron reduces seizure severity and associated memory deficit in PTZ-kindled animals. There is reduction in AChE activity and nitrite level as a putative downstream protective mechanism. 5-HT3 antagonist may be useful in the management of epilepsy and associated memory deficit. Abstract: Our previous studies have suggested a strong involvement of serotonergic innervations in epileptogenesis and associated memory impairment. Several studies have suggested that the modulation of 5-HT3 receptors could serve as a promising tool for the management of epilepsy and memory deficit. The present study was envisaged to confirm this hypothesis. In this study, kindling was induced in male Swiss Albino mice using a subconvulsive dose of pentylenetetrazole (PTZ) (35 mg/kg at 48 ± 2 h). Once the animals were kindled, they were treated with a vehicle, ondansetron (0.1, 0.5, 1 mg/kg/day; i.p.), m-chlorophenylbiguanide (m-CPBG) (1 mg/kg/day; i.p.), and ondansetron + m-CPBG for 20 days. On days 5, 10, 15, and 20, they were administered a PTZ challenging dose (35 mg/kg) to assess the seizure severity score; thereafter, memory was evaluated. After behavioral assessment on day 20, the animals were sacrificed and their brains were isolated to estimate cortical and hippocampal neurotransmitter levels (glutamate and gamma aminobutyric acid (GABA) by the high-performance liquid chromatography with the fluorescence detection method, and the nitrite level and acetylcholinesterase (AChE) activity by the microplate reader method). Ondansetron treatment significantly reduced the seizure severity and improved the acquisition performance in a dose-dependent manner. Neurochemical analysis suggested that ondansetron treatment significantly reduced the nitrite level and AChE activity in the cortex as well as in the hippocampus. The outcome of this study suggests the reduction in AChE activity and the nitrite level could be considered as protective mechanisms of ondansetron for amelioration of PTZ kindling and associated memory deficit.